Low-cost synthesis of high-quality graphene in do-it-yourself CVD reactor. (2nd October 2018) - Ereš, Zoran; Hrabar, Silvio
ABSTRACT: This paper reports design of a very low-cost (less than 2000 USD) chemical vapour deposition (CVD) reactor for graphene synthesis, based on readily available off-the-shelf components. The reactor is intended for in-house graphene synthesis in metamaterial research. The reactor was manufactured and tested, and synthesized graphene samples were characterized by Raman spectroscopy. Measurement results revealed high quality of synthesized single and multi-layer graphene samples.